The impact of the Coronavirus disease 2019 on hospitalizations for coronary artery revascularization: results from California State Inpatient Database. Issue 2 (22nd March 2023) - Rubens, Muni; Ramamoorthy, Venkataraghavan; Saxena, Anshul; Ruiz Pelaez, Juan Gabriel; Chaparro, Sandra; Jimenez, Javier
Abstract : Background: Coronavirus disease 2019 (COVID-19) outbreak has negatively impacted routine cardiovascular care. In this study, we assessed the impact of COVID-19 pandemic on percutaneous coronary artery intervention (PCI) and coronary artery bypass grafting (CABG) hospitalizations and outcomes using a large database. Methods: The current study was a retrospective analysis of California State Inpatient Database (SID) during March–December of 2019 and 2020. All adult hospitalizations for coronary artery revascularization were included for the analysis. ICD-10-CM diagnosis and procedure codes were used for identifying hospitalizations and procedures. The primary outcome was inhospital mortality, and secondary outcomes were hospital length of stay, stroke, acute kidney injury, and mechanical ventilation. Propensity score match analysis was done to compare adverse clinical outcomes. Results: PCI hospitalizations (relative decrease, 15.0%, P for trend <0.001) and CABG hospitalizations (relative decrease, 16.4%, P for trend <0.001) decreased from 2019 to 2020, while viral pneumonia hospitalizations increased (relative increase, 1751.6%, P for trend <0.001). Monthly PCI and CABG hospitalization showed decreasing trends from January 2019 to December 2020. Propensity score match analysis showed that the odds of inhospital mortality (OR, 1.12; 95% CI, 1.01–1.24), acute kidney injury (OR, 1.12; 95% CI, 1.06–1.17), and ARDS (OR, 1.89; 95% CI, 1.18–3.01) were higher among patients who received PCI in 2020. Conclusion: Results of our study indicate that initiatives such as encouraging patients to receive treatments and controlling the spread of COVID-19 should be instituted to improve PCI and CABG hospitalizations.